2010
DOI: 10.1007/s00027-010-0171-6
|View full text |Cite
|
Sign up to set email alerts
|

Movement of logperch—the obligate host fish for endangered snuffbox mussels: implications for mussel dispersal

Abstract: Unionid mussels are highly imperiled and the survival of their local populations is linked to the availability and dispersal potential of their host fish. We examined the displacement distance of logperch (Percina caprodes), which are obligate host fish for endangered snuffbox mussels (Epioblasma triquetra), to determine the dispersal potential by fish. Logperch in the Sydenham River, Ontario, Canada, were electrofished and marked with visible implant elastomer on five sampling dates during the gravid period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Similarly low short-term dispersal of host fishes has been reported for other lotic mussel species (McLain and Ross 2005). For example, the logperch, Percina caprodes, host for the snuffbox, Epioblasma triquetra, moved <75 m with no directional bias (Schwalb et al 2011), and many other small, benthic fishes that are important mussel hosts have similarly restricted movement (Petty and Grossman 2004). High site fidelity of mussel hosts would result in recruitment of most glochidia to their natal subpopulations, and the co-occurrence of juvenile and adult margaritiferids may reflect this local recruitment process (Hastie et al 2000, Arvidsson et al 2012.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly low short-term dispersal of host fishes has been reported for other lotic mussel species (McLain and Ross 2005). For example, the logperch, Percina caprodes, host for the snuffbox, Epioblasma triquetra, moved <75 m with no directional bias (Schwalb et al 2011), and many other small, benthic fishes that are important mussel hosts have similarly restricted movement (Petty and Grossman 2004). High site fidelity of mussel hosts would result in recruitment of most glochidia to their natal subpopulations, and the co-occurrence of juvenile and adult margaritiferids may reflect this local recruitment process (Hastie et al 2000, Arvidsson et al 2012.…”
Section: Discussionmentioning
confidence: 91%
“…Long-distance dispersal has been assumed to occur mainly during the larval stage via movements of host fishes because mussels are sedentary as adults and often form discrete, dense aggregations called mussel beds (Strayer, 2008;Schwalb et al, 2011a). However, despite that a growing body of evidence suggests extensive dispersal of fish species (Radinger & Wolter, 2014), contradictory results have been observed in natural mussel populations-potential host fishes rarely disperse more than a few hundred meters (McLain & Ross, 2005;Schwalb et al, 2011b;Terui et al, 2014a). Recent genetic studies using microsatellites also revealed limited gene flow among local populations of some mussel species (Geist & Kuehn, 2005;Kelly & Rhymer, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…All rights reserved and females are long-term brooders [12]. The life cycle of the snuffbox, like most mussels, begins when males release sperm into the water column and females take up the sperm with incoming water.…”
Section: Accepted Preprintmentioning
confidence: 99%